Martian Ice Revealed by Modeling of Simple Terraced Crater Formation. Issue 10 (2nd October 2020) - Martellato, E.; Bramson, A. M.; Cremonese, G.; Lucchetti, A.; Marzari, F.; Massironi, M.; Re, C.; Byrne, S.
Abstract: Arcadia Planitia, a region in the northern midlatitudes of Mars, displays an uncommonly high abundance of simple craters with a concentric morphology, which is indicative of layering beneath the surface. Radar measurements suggest that the near surface layers could be made of excess water ice. In this study, we select two of these impact structures of similar size ( D c 500 m), model their formation through iSALE shock physics code, and investigate the dependence of the final crater morphology on the material model parameters (cohesion and friction coefficient). Our parameter study shows that the intact and damaged cohesions of the nonporous ice play a fundamental role to obtain a good fit between our models and the topographic profiles taken from the digital terrain models in terms of crater diameter, crater wall inclination, and depth and size of the upper terrace. The central pit shape is instead controlled by the damaged friction coefficient of the basaltic crust, but it is mainly affected by projectile density and speed. Our results confirm that two layers of relatively pure water ice, each with different rheology and porosity, can explain the unique double‐terraced morphology of impact craters in Arcadia Planitia. The low values of cohesion we find for the ice might point to snowfall as emplacement mechanism in the region. The different thicknesses of the ice layers in the two crater areas seem to suggest variations in ice deposition and/or evolution history across Arcadia Planitia. Plain Language Summary: Impact craters are described by a bowl‐shaped morphology at smaller sizes. Any departure from such a shape provides insight into subsurface target properties, including changes in density, strength, water content, porosity, and composition. In particular, the presence of steps (or "terraces") along the walls of simple craters provides a straightforward example of complexity within the planetary crusts, and indicates an abrupt transition from upper, weaker layers to deeper, stronger material. Using numerical modeling, we studied two examples of terraced craters in Arcadia Planitia, Mars, to derive information about the rheological properties of the upper Martian crust. This analysis supports radar remote sensing measurements and suggests shallow ice‐rich layers in Martian midlatitudes terrains could plausibly cause the terraces observed in these craters. The distribution and properties of water ice are important for understanding Mars' climatic history, as well as the availability of in‐situ resources for future human exploration. Key Points: We performed numerical modeling to investigate the formation of simple craters with a concentric morphology on Mars The central pit dimensions are controlled both by the target material (damaged friction coefficient) and by the impactor (size and density) Our modeling shows water ice over basement bedrock can create wall terraces in simple craters